Community Perception as a Mediating Factor in Infrastructure Development: The Impact of Yogyakarta Southern Cross Road on Community Empowerment in Sanden District, Bantul Regency - Dessy Rachmawatie; Rifqi Maflahunaya (Penerbit Jurnal Indonesia, 2025)
This study aims to evaluate the extent to which public perception of the construction of the Southern Cross Road (SCR) influences community empowerment in Sanden District, Bantul Regency. Using a quantitative explanatory approach, the study involved 100 respondents selected using the Slovin formula and purposive sampling technique. Data collected through Likert-scale questionnaires and observations were analysed using paired sample t-tests and multiple linear regression. The findings indicate that residents responded very positively to the SCR project (mean 4.61). A difference test confirmed a significant increase in community empowerment post-development. Furthermore, perceptual variables, including accessibility, economic opportunities, and new identities, were shown to significantly influence community empowerment, both partially and simultaneously. This study concludes that positive community perception is a key element in achieving independence as a result of national infrastructure development.